Relations between sensory symptoms, touch sensation, and sensory neurography in the assessment of the ulnar neuropathy at the elbow. Issue 2 (February 2019) - Ginanneschi, Federica; Aretini, Alessandro; Mondelli, Mauro
Highlights: Little digit sensory anomalies are usual findings in ulnar neuropathy at elbow (UNE). Little digit neurographic/clinical anomalies have high predictivity for UNE diagnosis. Sensory anomalies are more frequent in predominantly axonal UNE. Abstract: Objectives: To evaluate sensitivity, specificity and predictive values of sensory findings in ulnar neuropathy at the elbow (UNE), differences according to UNE localization and pathophysiology, and relation between the sites of sensory symptoms, abnormal evaluation of sensation and neurographic findings of ulnar sensory nerve. Methods: Hand diagram and Semmes-Weinstein monofilaments were used for clinical evaluation in four ulnar hand territories. Sensory neurography was measured in the fourth and fifth digits-wrist segments (U5) and in the dorsal ulnar cutaneous nerve. Results: We enrolled 75 idiopathic UNE cases and 180 controls. Symptoms in the fifth digit, reduction of touch sensation and U5 sensory nerve action potential amplitude (SNAPa) had the highest sensitivity, specificity and predictivity in UNE diagnosis. The normal/abnormal sensory clinical findings of the fifth digit matched with normal/abnormal U5 SNAP more than the matching of sensory parameters in the other ulnar hand sites. Sensory anomalies were more frequent in predominantly axonal than demyelinating UNE. There were no differences according to UNE location. Conclusion: Sensory anomalies of the fifth digit are constant findings in UNE more than anomalies of the other ulnar nerve hand regions. Significance: Probably the fascicles from fifth digit are the most liable to damage at elbow.